Optical Memory Based on Conterpropagating Light in Microresonators - Bino, Leonardo Del; Moroney, Niall; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
A consequence of the Kerr effect in ring microresonators is that light can not always circulate simultaneously in both directions. Instead, under the appropriate conditions of input power and detuning, light can couple into the resonator only in one direction while the other continues on the coupling waveguide [1] - [3]. The two resulting light states, clockwise (CW) and counterclockwise (CCW), can be interpreted as the digital states 1 and 0 as shown in Fig. 1 (c). Microresonators have been theorized to be a suitable solution for on-chip logical processing and switching [4]. Here we present an all-optical bistable device based on the difference of the Kerr effect for co-propagating and counterpropagating light. The device does not require any electrical power, and relies only on a single laser input for its operation. The optical state is set by the dominant input power direction. The system exhibits hysteresis ( Fig. 1 (d) ) hence the optical state is maintained until an significant input in the opposite direction is received. The hysteresis provides resilience to fluctuations in the inputs up to half of the total input power.
CRIS-Team Scopus Importer:2021-10-29